Conflicting signals: A study on firms announcing share repurchases soon after seasoned equity offerings - Wang, Jin‐Ying (Accounting and finance (Parkville), 2025)
This study examines companies that announce open market share repurchases after seasoned equity offerings (SEO‐OMRs). This study finds that SEO‐OMRs have worse post‐OMR announcement returns, face a sharper decline in stock prices before OMR announcements, and have lower costs of buying back stocks. The study infers that firms announce an OMR soon after conducting an SEO to ensure market timing. The literature contains no evidence of SEO‐OMRs, and this study fills this gap. The findings of this study suggest that investors use SEOs as credible signals when deciding to purchase OMR stocks.